Enhancing Inclusive Learning Management through Video-Based Learning Media to Support SDG 4 for Hearing-Impaired Students - Setiyo Prajokoa; Shefa Dwijayati Ramadani; Weni Anggraeni (Journal of Current Studies in SDGs, 2027)
Objective: The study aimed to develop and evaluate video-based learning content integrated into an inclusive Learning Management System (LMS) ELITA to support students with hearing impairment in accessing Biology Learning Video Development courses. Specifically, this study examined the validity of the developed learning media and explored its effectiveness in facilitating the learning process for students with hearing impairment in an inclusive higher education environment. Method: The study employed a research and development (R&D) approach using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The research was conducted in July–August 2024 at Universitas Tidar, Central Java, Indonesia. Results: The findings showed that the developed video-based learning content integrated into LMS ELITA achieved a highly valid category based on evaluations from both material and media experts. During field implementation, students with hearing impairment were able to participate effectively in the learning activities and demonstrated positive responses toward the use of the inclusive LMS. The developed learning content provided better accessibility to learning materials by presenting information through visual-based media, supporting students with hearing impairment in understanding biological concepts and participating actively in the learning process. These findings indicate that the integration of accessible video-based content into an inclusive LMS can enhance learning experiences for students with hearing impairment. Novelty: The study contributes to the development of inclusive digital learning by integrating video-based learning content specifically designed to support students with hearing impairment within an LMS environment. The findings provide empirical evidence that inclusive LMS development can promote equitable learning opportunities and support the implementation of accessible education for students with disabilities.